99m Tc의 에너지 스펙트럼 변화에 따른 납 앞치마의 차폐 효과 평가 - 윤창용; Changyong Yoon; 지영식; Youngsik Ji (한국방사선학회 논문지, 2023)
핵의학과에서 가장 많이 사용되는 99m Tc를 점선원과 산란팬텀을 이용하여 에너지스펙트럼 변화를 분석하고 변화된 감마선 에너지에 따른 납 앞치마의 차폐효과를 평가하였다. 산란팬텀의 감마선 에너지 스펙트럼은 점선원보다 광전피크 영역은 감소하고 컴프턴 산란영역은 증가하였다. 감마선원 형태 변화에 따른 에너지 영역별 계수치는 점선원의 계수치보다 20 cm 거리에서 최대 66.1 %의 감소율을 보였으며 컴프턴 산란 영역에서는 산란팬텀의의 계수치가 점선원의 계수치보다 최대 40 cm 거리에서 122.2 % 증가하는 결과를 보였다. 감마카메라를 이용한 선원과 산란팬텀의 거리에 따른 차폐율 차이에서 광전피크 영역은 유사한 결과를 보였으나 컴프턴 산란영역에서는 20 cm거리에서 산란팬텀의 차폐율이 점선원의 차폐율보다 29.2% 증가하였으며 거리가 증가함에 따라 차폐율 차이는 감소하였다. 방사선 선량계를 이용한 납 앞치마 차폐율 측정에서 산란팬텀의 차폐율은 최대 15.3 %의 차이를 보였으며 거리가 증가할수록 두 선원의 차폐율 차이는 감소하였다. 산란팬텀의 납 앞치마 차폐율이 점선원보다 높고 선원과 가까운 거리일수록 납 앞치마의 효과는 증가하는 결과로 방사성의약품을 주입한 환자를 직접 대면할 때 납 앞치마의 착용은 방사선피폭 저감화에 도움이 될 것으로 판단된다. Changes in the energy spectrum were analyzed using 99m Tc as a point source and a scattering phantom, and the shielding effect of the lead apron according to the changed gamma ray energy was evaluated. In the gamma ray energy spectrum of the scattering phantom, the photo peak area decreased and the compton scattering area increased compared to the point source. The coefficients for each energy range according to the change in the shape of the gamma ray source showed a reduction rate of up to 66.1 % at a distance of 20 cm compared to the coefficient of the point source, and in the compton scattering area, the coefficient of the scattering phantom was 122.2 % at a distance of up to 40 cm compared to the coefficient of the point source. In the difference in shielding rate according to the distance between the source and the scattering phantom using a gamma camera, the photo peak area showed similar results, but in the Compton scattering area, the shielding rate of the scattering phantom at a distance of 20 cm increased by 29.2 % compared to the shielding rate of the point source. As the distance increased, the difference in shielding rate decreased. In measuring the shielding rate of the lead apron using a radiation dosimeter, the difference in the shielding rate of the scattering phantom was up to 15.3 %, and as the distance increased, the difference in the shielding rate between the two sources decreased. The shielding rate of the lead apron of the scattering phantom is higher than that of the point source, and the effectiveness of the lead apron increases as the distance to the source increases. As a result, wearing a lead apron when directly confronting a patient who has injected radioactive pharmaceuticals is expected to be helpful in reducing radiation exposure.